Maqashid Al-Shariah: Kerangka Adaptif Hukum Islam untuk Menjawab Tantangan Kontemporer - Nurhikmah, Nurhikmah (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2024)
This study aims to analyze the application of the Maqashid al-Shariah approach in establishing contemporary Islamic Law. Maqashid al-Shariah, which refers to the main objectives of Islamic law, includes protection of religion, soul, mind, descendants, and property. As a concept that prioritizes the welfare of the people, Maqashid al-Shariah has the potential to be the basis for making legal decisions that are relevant to the challenges of modern society. This study uses a qualitative approach with a library research method, reviewing academic literature, fatwas, and related legal documents issued by religious authorities. Data analysis was carried out through a thematic approach and content analysis to identify the main themes in the application of Maqashid al-Shariah. The results of the study show that the application of Maqashid al-Shariah in establishing Islamic Law provides flexibility in dealing with contemporary issues, such as Islamic economics, health, and human rights, without ignoring the basic principles of sharia. This application has also been proven to increase the relevance of Islamic Law in providing fair and humane solutions for Muslims in the era of globalization. This research is expected to enrich academic and practical understanding of Maqashid al-Shariah, as well as encourage further studies on this approach in various aspects of Islamic law in the future. [Penelitian ini bertujuan untuk menganalisis penerapan pendekatan Maqashid al-Shariah dalam penetapan Hukum Islam kontemporer. Maqashid al-Shariah, yang mengacu pada tujuan utama syariat Islam, meliputi perlindungan terhadap agama, jiwa, akal, keturunan, dan harta. Sebagai konsep yang memprioritaskan kemaslahatan umat, Maqashid al-Shariah memiliki potensi untuk menjadi dasar dalam pengambilan keputusan hukum yang relevan dengan tantangan masyarakat modern. Penelitian ini menggunakan pendekatan kualitatif dengan metode library research, mengkaji literatur akademik, fatwa, dan dokumen hukum terkait yang dikeluarkan oleh otoritas keagamaan. Analisis data dilakukan melalui pendekatan tematik dan analisis isi untuk mengidentifikasi tema-tema utama dalam penerapan Maqashid al-Shariah. Hasil penelitian menunjukkan bahwa penerapan Maqashid al-Shariah dalam penetapan Hukum Islam memberikan fleksibilitas dalam menghadapi isu-isu kontemporer, seperti ekonomi syariah, kesehatan, dan hak-hak asasi manusia, tanpa mengabaikan prinsip dasar syariat. Penerapan ini juga terbukti dapat meningkatkan relevansi Hukum Islam dalam memberikan solusi yang adil dan humanis bagi umat Muslim di era globalisasi. Penelitian ini diharapkan dapat memperkaya pemahaman akademik dan praktis mengenai Maqashid al-Shariah, sekaligus mendorong kajian lebih lanjut tentang pendekatan ini dalam berbagai aspek hukum Islam di masa depan].